Total synthesis of cyrneines A–B and glaucopine C - Guo-Jie Wu (Nature Portfolio, 2018)
Cyrneine diterpenoids represent a biologically important subfamily of cyathane-type diterpenoids. Here, the authors show new key steps to access their 5-6-7-tricyclic core and establish a more step-economic synthesis of cyrneine A and the first synthesis of cyrneine B and glaucopine C in a divergent manner.